Economic Impact of Revision Surgery for Proximal Junctional Failure After Adult Spinal Deformity Surgery: A Cost Analysis of 57 Operations in a 10-year Experience at a Major Deformity Center. Issue 16 (15th August 2016) - Theologis, Alexander A.; Miller, Liane; Callahan, Matt; Lau, Darryl; Zygourakis, Corinna; Scheer, Justin K.; Burch, Shane; Pekmezci, Murat; Chou, Dean; Tay, Bobby; Mummaneni, Praveen; Berven, Sigurd; et al.
Abstract : Study Design: Retrospective cohort analysis. Objective: To evaluate the economic impact of revision surgery for proximal junctional failures (PJF) after thoracolumbar fusions for adult spinal deformity (ASD). Summary of Background Data: PJF after fusions for ASD is a major cause of disability. Although clinical sequelae are described, PJF-revision operation costs are incompletely defined. Methods: Consecutive adults who underwent thoracolumbar fusions for ASD (August, 2003 to January, 2013) were evaluated. Inclusion criteria include construct from pelvis to L2 or above and minimum 6 months follow-up after the index ASD operation. Direct costs (surgical supplies/implants, room/care, pharmacy, services) were identified from medical billing data and calculated for index ASD operations and subsequent surgeries for PJF. Not included in direct cost data were indirect costs, charges, surgeon fees, or revision operations for indications other than PJF ( i.e., pseudarthrosis). Patients were compared based on the construct's upper-instrumented vertebra: upper thoracic (UT: T1–6) versus thoracolumbar junction (TLjxn: T9-L2). Results: Of 501 patients, 382 met inclusion criteria. Fifty-one patients [UT:14; TLjxn: 40 at index; average follow-up 32.6 months (6–92 months)] had revisions for PJF, which summed to 3.2 million total direct cost. Average direct cost of index operations for the cohort (68, 294) was significantly greater than PJF-revisions (55, 547). Compared with TLjxn, UT had a significantly higher average cost for index operations (79, 860 vs. 65, 868). However, PJF-revision cases were similar in average cost (UT:60, 103; TLjxn:53, 920; P = 0.09). Costs of PJF amounted to an additional 12.1% of the total index surgical cost in 382 patients. Conclusion: Revision operations for PJF after long thoracolumbar fusions for ASD are associated with an average direct cost of 55, 547 per case. Revision costs for PJF are similar based on the index procedure's upper-instrumented vertebra level. At a major tertiary center over a 10-year period, PJF came at a very significant economic expense amounting to 3.2 million for 57 cases. Level of Evidence: 3